Balancing motherhood and entrepreneurship: A phenomenological study of mumpreneur business restraining and enabling factors (Global Business Management Review (GBMR), 2024)
In Malaysia, women catalyze the growth of small and medium enterprises (SMEs). SMEs are increasingly important in maintaining economic growth and providing employment opportunities. The field of entrepreneurship is very dependent on the formation of individual capabilities in the business being undertaken, and these capabilities are significantly influenced by several restraining and enabling factors. This article explores the restraints and enablers that affect the business performance of managers from the Dapur Mawar project. A total of 15 mumpreneurs were involved in this study, selected through a purposive sampling technique. This study used semi-structured interviews, and the data were analyzed using thematic analysis. The study reveals several restraining factors: financial problems, societal stigma, and an imbalance between work and life. Meanwhile, the enabling factors include both internal and external elements, such as mindset, attitude, personality, competencies, government and agency support, and high-quality products and services. Overall, this study provides essential input on the factors that could determine the failure or success of a mumpreneur in their entrepreneurial activities. The findings proved that internal and external factors could play an essential role in the success of a mumpreneur.